MENELAAH RENCANA TATA RUANG KAWASAN PERKOTAAN DALAM PERSPEKTIF PEMERINTAHAN MEGAPOLITAN JABODETABEK-PUNJUR - Rizal, Jose (Fakultas Politik Pemerintahan, 2020)
The concept of developing a megapolitan area that includes Jakarta as a core city with buffer zones Depok, Bogor Raya, Tangerang Raya and Bekasi Raya has long been conceived by Jakarta Governor Ali Sadikin. This plan is to align the development of Jakarta which is predicted to be crowded and congested. At the end of the leadership of Jakarta Governor Sutiyoso (2007), the idea will be neatly packaged and broader socialized. Unfortunately, many oppose it because the surrounding satellite cities feel used for the benefit of Jakarta. Now, after 13 years have passed, the synchronization of the Jabodetabek-Punjur development must be done more seriously and directed. So that all local communities get a fair and equitable benefit.